2009
DOI: 10.1200/jco.2009.27.18_suppl.cra501
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of the oral PARP inhibitor olaparib in BRCA-deficient advanced breast cancer

Abstract: CRA501 Background: Olaparib (AZD2281; KU-0059436) is a novel, orally active PARP inhibitor that induces synthetic lethality in homozygous BRCA-deficient cells. A phase I trial identified 400 mg bd as the maximum tolerated dose (MTD) with an initial signal of efficacy in BRCA-deficient ovarian cancers (ASCO 2008; abst 5510). The primary aim of this study was to test the efficacy of olaparib in confirmed BRCA1/BRCA2 carriers with advanced refractory breast cancer. The secondary aim was to assess safety and tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 0 publications
1
85
0
4
Order By: Relevance
“…Such study was conducted in 54 patients (27 treated with olaparib 400 mg bid, 27 at the dose of 100 mg bid) with an objective response rate (ORR) of 41% and 22% respectively. PFS was 5.7 months in the cohort with 400 mg bid and 3.8 in the cohort with 100mg bid [31,32]. A good tolerability of the treatment was reported with grade 3 or higher toxicities seen in 5 patients in terms of fatigue, nausea and anemia.…”
Section: Olaparibmentioning
confidence: 87%
“…Such study was conducted in 54 patients (27 treated with olaparib 400 mg bid, 27 at the dose of 100 mg bid) with an objective response rate (ORR) of 41% and 22% respectively. PFS was 5.7 months in the cohort with 400 mg bid and 3.8 in the cohort with 100mg bid [31,32]. A good tolerability of the treatment was reported with grade 3 or higher toxicities seen in 5 patients in terms of fatigue, nausea and anemia.…”
Section: Olaparibmentioning
confidence: 87%
“…In a phase II trial of heavily pretreated patients with recurrent, measurable, chemotherapy-refractory BRCA mutation-associated breast cancer, the PARP inhibitor olaparib (400 mg twice daily and subsequently 100 mg twice daily) demonstrated measurable single-agent efficacy, with an ORR as high as 41% [60]. Like BRCA-associated breast cancers, triple-negative breast cancer is sensitive to PARP inhibition in the presence of platinum-based chemotherapy.…”
Section: Poly(adp Ribose) Polymerase Inhibitorsmentioning
confidence: 99%
“…There is also a study that has demonstrated the therapeutic efficacy of treatment in advanced breast cancer. In a phase II trial, the efficacy of the oral poly (ADP-ribose) polymerase inhibitor olaparib in BRCA-deficient advanced breast cancer was evidenced [21].…”
Section: Genetic Counseling and Management Of Women With Hereditary Bmentioning
confidence: 99%